SISTEM INFORMASI PENJUALAN HASIL PERTANIAN BERBASIS WEB ( Studi Kasus di UD Fajar Hasil Bumi) - Naga, Akfarius Sawa (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2022)
Fajar hasil Bumi is one of the largest commodity transaction warehouses on the island of Flores, which is located at km4, Mautapaga Village. Ende Regency. To note, apart from Ende Regency, Fajar Prestasi Bumi also has a branch located in Kewa Pante, Sikka Regency. where the farmers will sell their agricultural products to the warehouse and then carry out a sale and purchase transaction at a predetermined price. Commodity-producing farmers come from various regions. This study uses the Waterfall method by following the various stages in it. In this study, testing was also carried out using the Black Box method. The results of this study indicate that there is still a lack of application of information systems in sales and the quality of sales reports from both product data and purchase data is still low. With the existence of an information system selling agricultural products, hopefully product data collection and sales information can be helped. sales business owners still do not understand the use of the system and there is no socialization regarding the use of information systems to sales business owners such as at UD Fajar Prestasi Bumi. Keywords: sales, Information Systems, Reports, Waterfall, Black Box.